Dermatological Infectious Diseases Prevalence at Dermatology-Venereology Outpatient Clinics of Hospitals in Medan - Yosi, Ariyati; Fujiati, Isti Ilmi; Yulfi, Hemma; Nasution, Irina Kemala (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Skin infections are common in developing countries but are often not considered a significant health problem. One cause of this condition is a lack of epidemiological information about the prevalence and/or severity of the disease. This study aims to determine the prevalence and proportion of infectious skin diseases based on gender and age in the teaching hospitals at the Faculty of Medicine, Universitas Sumatera Utara, Medan, Indonesia. Methods. A descriptive-retrospective method was used in this study and the data were obtained from the medical records of patients at the dermatology and venereology polyclinic at Adam Malik Hospital and Prof. Dr. Chairuddin P. Lubis Universitas Sumatera Utara Hospitaletween 2017 and 2019. Results. A total of 12,686 patients were enrolled in this study, 26% were diagnosed with infectious skin disease with a total of 3,297 cases. Based on gender, patients were more dominated by men (55%) than women (45%). Most patients with infectious skin diseases were in the late adolescent age group or 17–25 years (20.4%) and the least were in the 0–4 years age group (3.2%). Furthermore, fungi were the dominant causative agent, which accounts for 51.5% of all cases. Conclusion. Infectious skin disease is a skin disease that is often found, especially in men and the age group of 17–25 years.